EKSPLORASI IN SILICO GEN rbcL PADA Dioscorea alata: KERAGAMAN GENETIK UNTUK KETAHANAN PANGAN MASA DEPAN - Wa Ode, Kamillah (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
Global food security is increasingly threatened by climate change, land degradation, and the heavy dependence on rice as the principal staple food. Diversification through the utilization of local commodities offers a strategic solution, with Dioscorea alata L. (purple yam), a tuberous crop rich in carbohydrates and anthocyanins and exhibiting high adaptability to diverse agroecological conditions, presenting significant potential. This study aimed to investigate the genetic diversity of D. alata through an in silico approach, employing the rbcL gene as a molecular marker, with sequence data retrieved from the public NCBI database. Analytical procedures included BLAST alignment, multiple sequence alignment, phylogenetic tree construction, 3D protein structure prediction, and functional annotation. The findings revealed that the rbcL gene in D. alata is highly conserved, with 100% sequence identity among accessions, suggesting pronounced genetic homogeneity likely resulting from long-term domestication. In contrast, sequence variation among other Dioscorea species indicated evolutionary divergence. The predicted protein structure displayed a predominance of alpha helices, supporting structural stability critical for photosynthetic function. Additionally, the rbcL gene was located within the active domain of the RuBisCO enzyme, essential for carbon fixation in the Calvin cycle. Thus, while rbcL is effective for evolutionary studies and interspecies identification, complementary markers such as matK or ITS are recommended for resolving intraspecific genetic diversity. The present findings are anticipated to contribute to the conservation and breeding strategies of D. alata in support of future food security initiatives. Keywords: Dioscorea alata, rbcL, DNA barcoding, food security